2022
DOI: 10.7150/jca.57457
|View full text |Cite
|
Sign up to set email alerts
|

Can the Gene Expression Profile of Patients with Acute Myeloid Leukemia Predict Complete Remission Following Induction Therapy?

Abstract: Recent advances in sequencing technologies and genomics have led to the development of several targeted therapies such as BCL2 and Bromodomain and extra-terminal (BET) protein inhibitors for a more personalized treatment of patients with acute myeloid leukemia (AML), yet the majority of patients still receive standard induction chemotherapy. The molecular profiles of patients who are likely to respond to induction therapy and novel directed therapies remain to be determined. The expression of AML-related genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Malignant blasts have the ability to evade apoptosis via the constitutively elevated expression of antiapoptotic proteins of the BCL-2 family. Molecular studies have confirmed these observations and demonstrated the prognostic impact of high levels of expression of BCL2, measured by immunohistochemistry [10] or mRNA quantification [11,12]. Moreover, high levels of BCL-2 family proteins are associated with resistance to chemotherapy [10,13,14].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Malignant blasts have the ability to evade apoptosis via the constitutively elevated expression of antiapoptotic proteins of the BCL-2 family. Molecular studies have confirmed these observations and demonstrated the prognostic impact of high levels of expression of BCL2, measured by immunohistochemistry [10] or mRNA quantification [11,12]. Moreover, high levels of BCL-2 family proteins are associated with resistance to chemotherapy [10,13,14].…”
Section: Introductionmentioning
confidence: 84%
“…The expression of other genes may also have prognostic value. In fact, several multi-gene scores have been developed to predict which AML patients, achieving complete remission (CR) in response to standard induction therapy, will have longer survival [12,40,41]. The application of these scores may help distinguish patients who will require a cell therapy-based approach from those who are chemosensitive and thus might avoid allogeneic hematopoietic stem cell transplantation (HSCT).…”
Section: Role Of Apoptosis In Leukemogenesismentioning
confidence: 99%